The entrepreneurial shift : - Locke, Robert R. (Cambridge University Press, 2004)
The Entrepreneurial Shift is an impressive achievement and makes an outstanding contribution to the literature on management education. This book is a demonstration, based on an international study, that technology changes and American entrepreneurial culture play a key role in shaping educational systems both inside and outside the USA